Production of clean hydrogen by electrochemical reforming of oxygenated organic compounds - Lamy, C. (Claude) (Hydrogen and fuel cells primers., 2020)
Production of Clean Hydrogen by Electrochemical Reforming of Oxygenated Organic Compounds provides a comprehensive overview of the thermodynamics and experimental results that allow the decomposition process of organic compounds leading to hydrogen to be carried out at working cell voltages much lower than those encountered in water electrolysis. The authors review different methods of synthesis and characterization of the catalysts needed to activate the electro-oxidation reaction and describe different electrolysis experiments that produce hydrogen in a Proton Exchange Membrane Electrolysis Cell (PEMEC). Other sections investigate the effect of the nature of the reactive molecules, the nature and structure of the catalysts, and more. By exploring the link between organic oxidation/conversion to hydrogen production, this book fills a gap in the existing literature and provides researchers in the field with an authoritative and comprehensive reference they can use when developing new sustainable processes and systems for hydrogen production. --